Assemblies of Christians in the Wirral : a look at their history -- the beginnings, growth, and sadly, in some cases their declension and closure -- by one who has been connected with them for 88 years ; also includes a history of Rice Thomas Hopkins - Bresnen, Fred (Leeswood, UK : Fred and Audrey Bresnen, 2002)
"A look at their history, the beginnings, growth, and sadly, in some cases their declension and closure, by one who has been connected with them for 88 years, also includes a History of Rice Thomas Hopkins" T. p.
A gift from the author to Mr Ian McDowell, signed.
Keywords: Hopkins, Rice Thomas, -- 1842-1916.; Brethren movement -- England -- Wirral Peninsula -- history